UMP upgrades IT applications system - UMP, PNC
Universiti Malaysia Pahang (UMP) has recently upgraded its Oracle 11gR2 database and the information infrastructure applications system, Oracle Real Application Cluster (RAC), in line with the university’s requirements to enhance its information technology (IT) capability and ensure its long-term viability and effectiveness.